Peningkatan Academic Performance Melalui Digital Capability dan Digital Citizenship Mahasiswa Pendidikan Tinggi Vokasi Di Indonesia - Nur Ahmad Budi Yulianto; Ahmad Afendy Susanto (Universitas Kristen Indonesia Toraja, 2024)
Academic performance is currently an interesting topic of conversation among academics. Even though academic performance has a positive impact it also has a negative impact on academic performance. Therefore, the role of digital citizenship is needed to prevent the negative impact of digital capability on academic performance among students. This research aims to analyze the influence of digital capability on academic performance with digital citizenship as a moderating variable. The population in this study was 274 second year fourth and sixth year students at vocational colleges. The sample was determined using stratified random sampling with the number of samples taken using the Slovin technique so that the sample obtained was 162 students. Data were analyzed using SEM-PLS via WarpPLS 7.0 software. The research results show that digital capability has a significant effect on academic performance. However, digital citizenship is not a moderating variable in the influence of digital capability on academic performance. This study encourages vocational college leaders to carry out more intense digital citizenship outreach so that students' digital capability can increase academic performance to the maximum.